University research alliances, absorptive capacity, and the contribution of startups to employment growths - Andrew A. Toole; Dirk Czarnitzki; Christian Rammer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
This paper examines how university research alliances and other cooperative links with universities contribute to startup employment growth. We argue that 'scientific absorptive capacity' at the startup is critical for reaping the benefits from university research alliances, but not necessarily for other university connections. We also estimate the aggregate employment contribution from startup firms and attribute those employment gains to university research alliances and other university connections. We find significant contributions to employment growth from university research alliances and other university connections, but scientific absorptive capacity is critical for university research alliances. Only 7% of the startup population maintained a university research alliance, but among these firms, 3.4% of their total jobs created were attributable to their alliances. These results suggest university connections are quite important for job growth and university research alliances contributed substantially to job creation for those firms that had such alliances.
Keywords: L25; L26; J24; 330; Academic Entrepreneurship; Startups; Firm performance; Technology Transfer; University Spinoff Policy; Human Capital